A simple route to highly active single-enzyme nanogels. Issue 4 (11th December 2017) - Beloqui, Ana; Kobitski, Andrei Yu; Nienhaus, Gerd Ulrich; Delaittre, Guillaume
Abstract : Just add sugar: the synthesis of single-enzyme nanogels, a class of highly robust nanobiocatalysts, is boosted by the addition of carbohydrates. Our methodology is demonstrated with a dozen commercial proteins, spanning a large size interval and a broad domain of applications. In addition, new in-depth structural characterizations are provided. Abstract : We have established a simple one-step synthesis of single-enzyme nanogels (SENs), i.e., nanobiocatalysts consisting of an enzyme molecule embedded in a hydrophilic, polymeric crosslinked nanostructure, as a most attractive approach to enhance the stability of enzymes. In contrast to earlier protocols, we demonstrate here that the addition of a small amount of sucrose makes the nanogel formation equally effective as earlier two-step protocols requiring enzyme pre-modification. This provides the dual advantage of skipping a synthetic step and preserving the surface chemistry of the enzymes, hence their native structure. Enzymes encapsulated in this way exhibit a high catalytic activity, similar to that of the free enzymes, in a markedly widened pH range. With our method, the thickness of the hydrogel layer can be finely tuned by careful adjustment of reaction parameters. This is most important because the shell thickness strongly affects both enzyme activity and stability, as we observe for a wide selection of proteins. Finally, a single-molecule analysis by means of two-color confocal fluorescence coincidence analysis confirms that our encapsulation method is highly efficient and suppresses the occurrence of nanoparticles lacking an enzyme molecule. The proposed method is therefore highly attractive for biocatalysis applications, ensuring a high activity and stability of the enzymes.